2018
DOI: 10.12697/fce.2018.55.14
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of lichens and allied fungi on Norway spruce (Picea abies) in the middle boreal forests of Republic of Karelia (Russia)

Abstract: A detailed study of lichen diversity and estimation of epiphytic lichen cover characteristics on spruce as a key ecosystem component was performed in boreal forests of Karelia (NW Russia). The aims of the present paper are: (1) to study lichen diversity on Norway spruce in the middle boreal forests of southern Karelia (NW Russia), and (2) to estimate the main characteristics of epiphytic lichen cover on spruce trunks and branches. In total, 158 species of lichens and allied fungi were found on spruce, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
3
0
4
Order By: Relevance
“…Despite more than 25 years of lichenological studies in Vodlozersky National Park, only scattered data can be found in various sources which mainly describe the lichen diversity of the Karelian part (Tarasova & Stepanova, 2001;Ignatenko & Tarasova, 2017;Androsova et al, 2018). Description of the history of lichenological studies in this territory is provided in .…”
Section: Introductionmentioning
confidence: 99%
“…Despite more than 25 years of lichenological studies in Vodlozersky National Park, only scattered data can be found in various sources which mainly describe the lichen diversity of the Karelian part (Tarasova & Stepanova, 2001;Ignatenko & Tarasova, 2017;Androsova et al, 2018). Description of the history of lichenological studies in this territory is provided in .…”
Section: Introductionmentioning
confidence: 99%
“…Androsova et al, 2018) обширный гербарный материал. В результате данной работы список лишайников карельской части НП «Водлозерский» увеличился на 62 вида.…”
unclassified
“…При этом среди эпифитов Populus tremula L. были обнаружены 51 новый вид, а среди эпифитов Picea sp. -10 новых видов лишайников(Androsova et al, 2018). Lepraria ecorticata (J.R. Laundon) �uk�a и Micarea fallax Launis & Myllys(Tarasova et al, 2020a), а также новые виды для Европейской России: Накопление данных по числу видов и подвидов лишайников и близкородственных грибов на территории национального парка «Водлозерский» по годам исследований.Fig.…”
unclassified
“…В настоящее время для территории Ботанического сада ПетрГУ отмечено 264 видов лишайников и близкородственных грибов (Тарасова и Сонина, 2006;Tarasova et al, 2013;Серапионова, Сонина, 2017;Андросова и др., 2017;Androsova et al, 2018). Это составляет 70 % видового состава лишайников Петрозаводского городского округа, насчитывающего 382 вида, среди которых 95 (24 %) обнаружены только в пределах Ботанического сада ПетрГУ (Tarasova et al, 2013(Tarasova et al, , 2015Тарасова и др., 2016).…”
unclassified
“…Результаты сравнения показателей эпифитного лишайникового покрова хвойных интродуцентов Ботанического сада с его значениями на стволах основных лесообразующих хвойных пород в южной Карелии показали, что значения общего проективного покрытия лишайников у основания ствола Picea abies (L.) Karst. в лесных сообществах южной Карелии выше (59 %), а покрытие на высоте 130 см по значениям сравнимо одинаково (Androsova et al, 2018). Различия в общем покрытии лишайников для деревьев рода Pinus были выявлены в значениях общего проективного покрытия на высоте 130 см, более высокие значения которого зафиксированы в арборетуме (Тарасова, Горшков, 2000).…”
unclassified